2018
DOI: 10.1021/acs.molpharmaceut.7b00892
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Optimization and Structural and Thermal Characterization of the Antimicrobial Abietane 7α-Acetoxy-6β-hydroxyroyleanone

Abstract: The abietane 7α-acetoxy-6β-hydroxyroyleanone (AHR), obtained from plant extracts, is an attractive lead for drug development, given its known antimicrobial properties. Two basic requirements to establish any compound as a new drug are the development of a convenient extraction process and the characterization of its structural and thermal properties. In this work seven different methods were tested to optimize the extraction of AHR from Plectranthus grandidentatus. Supercritical fluid extraction (SFE) proved t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 40 publications
4
31
1
Order By: Relevance
“…The compound Diroy is the less bioactive abietane and this is in agreement with the more polar feature on the C-6 and C-7 positions. This polar structure-activity relationship could be explained due to a better membrane interaction [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The compound Diroy is the less bioactive abietane and this is in agreement with the more polar feature on the C-6 and C-7 positions. This polar structure-activity relationship could be explained due to a better membrane interaction [11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 98%
“…Numerous studies attribute these biological properties to the diterpenes expressed by this genus [8][9][10]. Our previous studies have demonstrated that the diterpenes isolated from Plectranthus genus induce apoptosis in various cancer cell lines, including human myeloid leukaemia, and pancreatic, lung, melanoma, prostate, and breast cancer [11][12][13][14][15][16][17]. The present study focuses on the properties of abietane diterpenes (Roy, Deroy, Diroy, and Parv D) isolated from P. madagascariensis and P. ecklonii.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Version 1.1, 2013). The extraction and isolation process of 1 and 2 were performed according to Garcia et al (2018) and Bernardes et al (2018), respectively. Isca et al (2020).…”
Section: Plant Materialsmentioning
confidence: 99%
“…The obtained organic extracts were filtered, and the solvent was removed by rotary evaporation [9]. The supercritical fluid extraction (SFE) was done as previously described [20].…”
Section: P Ecklonii Extracts Preparationmentioning
confidence: 99%